2021
DOI: 10.1093/molbev/msab195
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolutionary Dynamics of Energy Limited Microorganisms

Abstract: Microorganisms have the unique ability to survive extended periods of time in environments with extremely low levels of exploitable energy. To determine the extent that energy limitation affects microbial evolution, we examined the molecular evolutionary dynamics of a phylogenetically diverse set of taxa over the course of 1,000 days. We found that periodic exposure to energy limitation affected the rate of molecular evolution, the accumulation of genetic diversity, and the rate of extinction. We then determin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 63 publications
(85 reference statements)
1
18
1
Order By: Relevance
“…Similar to a previous analysis [31], it is likely that gene identity was again too coarse a measure to determine whether convergent or divergent evolution occurred. While ∆spo0A is a master regulatory gene, its removal may only have slightly perturbed the rates of evolution for a large number of genes in a given environment.…”
Section: Parallelism and (Con/di)vergence At The Gene Levelmentioning
confidence: 67%
See 4 more Smart Citations
“…Similar to a previous analysis [31], it is likely that gene identity was again too coarse a measure to determine whether convergent or divergent evolution occurred. While ∆spo0A is a master regulatory gene, its removal may only have slightly perturbed the rates of evolution for a large number of genes in a given environment.…”
Section: Parallelism and (Con/di)vergence At The Gene Levelmentioning
confidence: 67%
“…S5,6), suggesting that, generally, the direction of evolution at the gene-level tended towards convergence rather than divergence. We found that this is the case, as the degree of overlap in enriched genes relative to a null distribution [31] suggests convergent evolution (Fig. S9).…”
Section: Parallelism and (Con/di)vergence At The Gene Levelmentioning
confidence: 76%
See 3 more Smart Citations